Canine D163-PrP polymorphic variant does not provide complete protection against prion infection in small ruminant PrP context - Alba Marín-Moreno (Nature Portfolio, 2021)
Abstract E/D163 polymorphism of dog prion protein (PrP) has been recently proposed as the variant responsible for canid prion resistance. To further investigate the protective role of this variant against prion replication, the transgenic mouse model OvPrP-Tg532 expressing sheep/goat PrP carrying the substitution D162 (equivalent to D163 position of dog PrP) was generated and intracranially inoculated with a broad collection of small ruminant prion strains. OvPrP-Tg532 mice showed resistance to classical bovine spongiform encephalopathy (BSE) from sheep and some classical scrapie isolates from sheep and goat but were susceptible to ovine atypical L-BSE and numerous classical scrapie isolates. Strikingly, some of these classical scrapie isolates showed a shift in their prion strain properties. These results suggest that other PrP residues apart from E/D163 variant of dog PrP or factors distinct than PrP may participate in prion resistance of canids and that different factors may be required for D162 sheep PrP to provide effective protection to sheep against ruminant prions.